Analisis Faktor Yang Mempengaruhi Minat Siswa Kelas IX MTs Al-Ma’arif dalam Pemilihan Sekolah Lanjutan - Amir, Nadia Lathifa; Suwena, Kadek Rai (Universitas Pendidikan Ganesha, 2023)
The aims of this study are 1) to determine the factors that influence the interest of class IX students at MTs Al-Ma`'arif in the selection of secondary schools and 2) to determine the most dominant factors influencing student interest in the selection of secondary schools. This type of research is factorial research. The population in this study were 72 students of class IX MTs Al-Ma `arif. The sampling technique used was a saturated sampling technique so that the entire population was used as a sample. The data collection method in this study used a questionnaire and interview instruments. The analysis used in processing the data is descriptive analysis and factor analysis. The results of this study are (1) the factors that influence the interest of class IX students at MTs Al-Ma' arif in the selection of secondary schools are physical, psychological, fatigue, family, school, and community, and (2) the most dominant factors influencing interest in students in the selection of secondary schools are psychological, with a variance value of 65.841 and a loading factor of 0.988.